Logiques méritocratiques et “barrière de la langue” : modes d’accès à la formation à la langue majoritaire des migrants dans une ville française et une ville anglaise - Joanne Walker (Cahiers de la Recherche sur l'Education et les Savoirs)
In France, despite the barrier that the French language can represent for adults socialized abroad in other languages, publicly funded language training is not available for all those who wish to enrol but is aimed at priority groups which change periodically. International comparison, here with England, allows us to question this state of affairs, its origins and its consequences. Based on a study in a French and an English city between 2010 and 2015, this article shows how different categories articulating gender, nationality, level of training, length of immigration and administrative status determine access to language training and certification in each city. While analysing the organisation, in both cities, of language training in unequally resourced spaces, it explores the role envisaged for language provision in the distribution of social positions.